Patterns of Domain-Specific Learning Among Medical Undergraduate Students in Relation to Confidence in Their Physiology Knowledge: Insights From a Pre–post Study - Roeper, Jochen; Reichert-Schlax, Jasmin; Zlatkin-Troitschanskaia, Olga; Klose, Verena; Weber, Maruschka; Nagel, Marie-Theres (Frontiers in Psychology, 2022)
Research Focus The promotion of domain-specific knowledge is a central goal of higher education and, in the field of medicine, it is particularly essential to promote global health. Domain-specific knowledge on its own is not exhaustive; confidence regarding the factual truth of this knowledge content is also required. An increase in both knowledge and confidence is considered a necessary prerequisite for making professional decisions in the clinical context. Especially the knowledge of human physiology is fundamental and simultaneously critical to medical decision-making. However, numerous studies have shown difficulties in understanding and misconceptions in this area of knowledge. Therefore, we investigate (i) how preclinical medical students acquire knowledge in physiology over the course of their studies and simultaneously gain confidence in the correctness of this knowledge as well as (ii) the interrelations between these variables, and (iii) how they affect the development of domain-specific knowledge. Method In a pre–post study, 169 medical students’ development of physiology knowledge and their confidence related to this knowledge were assessed via paper-pencil questionnaires before and after attending physiology seminars for one semester. Data from a longitudinal sample of n = 97 students were analyzed using mean comparisons, regression analyses, and latent class analyses (LCAs). In addition, four types of item responses were formed based on confidence and correctness in the knowledge test. Results We found a significant and large increase in the students’ physiology knowledge, with task-related confidence being the strongest predictor (apart from learning motivation). Moreover, a significantly higher level of confidence at t2 was confirmed, with the level of prior confidence being a strong predictor (apart from knowledge at t2). Furthermore, based on the students’ development of knowledge and confidence levels between measurement points, three empirically distinct groups were distinguished: knowledge gainers, confidence gainers, and overall gainers. The students whose confidence in incorrect knowledge increased constituted one particularly striking group. Therefore, the training of both knowledge and the ability to critically reflect on one’s knowledge and skills as well as an assessment of their development in education is required, especially in professions such as medicine, where knowledge-based decisions made with confidence are of vital importance.